Improving habitat exchange planning through theory, application, and lessons from other fields. Issue 73 (July 2017) - Galik, Christopher S.; BenDor, Todd K.; DeMeester, Julie; Wolfe, David
Highlights: New tools are being deployed to address the continued decline of at risk species. Considerable resources have been devoted to habitat exchanges with mixed success. Lessons have been slow to translate from other planning arenas (e.g., electricity). Transfer of knowledge and experience across disciplinary bounds is necessary. Abstract: New tools are being deployed to address the continued decline of species at risk of becoming threatened or endangered. One approach receiving increased attention is the habitat exchange, or the use of a market-based, landscape-scale approach to protect or restore habitat in one place to offset impacts elsewhere. Although considerable resources have been devoted to the establishment of habitat exchanges over the past several years, actual implementation of transactions through habitat exchanges have been limited. As we argue here, important lessons have been slow to translate to habitat exchanges from other planning arenas. We briefly outline how the decision sciences, particularly structured decision making, and other planning processes − such as those governing electricity infrastructure development − can provide examples to facilitate the use of habitat exchanges as a viable and scalable conservation tool. We emphasize the challenge of translating theory to application, and note the importance of cross-fertilization of knowledge and experience across traditional disciplinary bounds.